The Influence of TikTok Influencers' Korean Visual Style on University Students' Purchase Intention - Salwa Nur Aulia; Tita Adysti; Ahmad Maulana (International Journal Administration, Business & Organization, 2026)
The rapid growth of the Korean Wave and the increasing popularity of TikTok have significantly transformed the digital marketing landscape. This study aims to examine the influence of Korean-style visual aesthetics displayed by TikTok influencers on university students’ purchase intention. A quantitative approach was employed using a survey method, with data collected through an online questionnaire distributed to active university students who use TikTok and have been exposed to Korean-style aesthetic content. The collected data were analyzed using validity and reliability tests, classical assumption tests, and simple linear regression analysis. The findings indicate that Korean-style visual aesthetics have a positive and significant influence on students’ purchase intention. The visual elements presented by TikTok influencers were found to attract attention, create positive perceptions, and encourage stronger intentions to purchase promoted products. These results suggest that Korean-inspired visual aesthetics serve as an effective marketing stimulus in shaping consumer responses within digital platforms. The study concludes that the use of Korean-style visual aesthetics by TikTok influencers can enhance purchase intention among university students and provides insights for marketers seeking to leverage visual-based promotional strategies in social media marketing.